MUJIKA Luis Maria. Barne ibilerak (1985-1996): Hiria argit. 2001 urtea, 381 or. - Otxoteko, Pello (EGAN, 2021)
PELLO OTXOTEKO: MUJIKA Luis Maria. Barne ibilerak (1985-1996) Hiria argit. 2001 urtea, 381 or.